Ligand-enabled C–H borylation of diverse classes of arenes - Md Emdadul Hoque; Sayan Dey; Mirja Md Mahamudul Hassan; Jagriti Chaturvedi; Saikat Guria; Jaitri Das; Brindaban Roy; Buddhadeb Chattopadhyay (Tetrahedron Chem, 2022)
Here we report a new 6,6′-bipyridine based ligand framework for the iridium-catalysed regioselective ortho borylation of diverse classes of arenes containing different functional groups. Moreover the developed method is highly selective for the directed C(sp (Altus and Love, 2021) [3]-H borylation of the 2-pyridyl amines as well as benzyl and homobenzyl amides directed by pyridine group and amide directed borylation of N-adjacent C–H bond of amides.